The Analisis Jumlah Penduduk, Tingkat Pendidikan dan Ekonomi Terhadap Pengangguran di Kabupaten Lombok Barat: Analysis of Population, Education and Economic Levels on Unemployment in West Lombok Regency - Ni Luh Moning; Muhammad Sayuti; Ahmad Suhendri (JURNAL EKONOMI, BISNIS DAN PARIWISATA, 2025)
One of the challenges in national development is the unemployment rate, this is due to differences in natural resources, human resources, and opportunities to improve the standard of living in society. The discovery of information and electronic technology as the beginning of the industrial revolution 3.0 took a long time, as did the industrial revolution 4.0 with digital technology that dominates and develops rapidly. The impact of technological developments is that disruption occurs. Economic disruption can cause the loss of a number of jobs. The industrial revolution 4.0 has an impact on the disappearance of almost 50 million people who will become unemployed, especially in Indonesia. The relationship between economic growth and unemployment can be explained by Okun's Law, which is taken from the name of Arthur Okun, which states that there is an empirical influence between unemployment and output in the business cycle. The results of the empirical study show that adding 1 (one) point of unemployment will reduce GDP (Gross Domestic Product) by 2%. This means that there is a negative influence between economic growth and unemployment and vice versa, namely unemployment on economic growth. This research is quantitative research with a literature study approach. This research will use secondary data as the main research data. The data used is data from the West Lombok Regency Central Statistics Agency for 2021, 2022 and 2023. As a strong reference support, researchers use journals, books and similar previous research. Research data was analyzed by multiple regression to determine the relationship between research variables. The research was carried out in West Lombok Regency in 2023 from October to December. Based on data from the West Lombok Regency Central Statistics Agency from 2021-2023 the average population growth rate was 1.82%. Apart from the rate of population growth, an indicator of a nation's success is the education level of its population. More advanced education means it will bring various positive influences to the future in various areas of life. The population of West Lombok Regency who have completed education up to bachelor's level in the last three years is 4.67% with an average of 0.31%. From the results of research data processing, it was found that the dominant variable is economic growth. This can be seen from the largest coefficient value, namely 3.086. This indicates that the economic growth variable is the most dominant variable influencing economic growth in West Lombok Regency from 2021-2023. From the discussion of the research results, it can be concluded that partially the influence of the independent variable on the dependent variable is that the population is not significant on the number of unemployed. Meanwhile, the Education Level and economic growth variables have a significant impact, meaning that the two variables above have an impact on the unemployment rate.